2011
DOI: 10.1007/s12195-011-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology of Erythrocytes from Adult Mice Homozygous for a Targeted Disruption of the E-Tmod Gene at Exon 1

Abstract: The erythrocyte membrane skeleton is a protein network that provides deformability and stability to erythrocytes. Defects in the network lead to dysfunction and diseases. Erythrocyte tropomodulin (E-Tmod) of 41 kDa is an actin-capping protein at the slow-growing end, and together with tropomyosin 5 or 5b, has been proposed to form a ''molecular ruler'' dictating the length of actin protofilament of 37 nm in the network. We have previously created an E-Tmod knockout mouse model by targeted disruption of exon 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While Tmod1 -/- mice died at embryonic day 9.5, the heterozygous Tmod1 +/- mice were able to mate with a cardiac specific Tmod1 overexpressing transgenic (TOT) mice ( 37 ). Interbreeding between their offsprings resulted in TOT/Tmod1 -/- mice where the overexpression of Tmod1 in the heart rescued the homozygosity’s lethality ( 38 ). TOT/Tmod1 -/- mice were transferred from Dr. L. Amy Sung’s lab to the Peking University Health Science Center and maintained in SPF animal room.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Tmod1 -/- mice died at embryonic day 9.5, the heterozygous Tmod1 +/- mice were able to mate with a cardiac specific Tmod1 overexpressing transgenic (TOT) mice ( 37 ). Interbreeding between their offsprings resulted in TOT/Tmod1 -/- mice where the overexpression of Tmod1 in the heart rescued the homozygosity’s lethality ( 38 ). TOT/Tmod1 -/- mice were transferred from Dr. L. Amy Sung’s lab to the Peking University Health Science Center and maintained in SPF animal room.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we demonstrated that Tmod1 is expressed in bone marrow-derived dendritic cells (BMDCs) and is upregulated upon lipopolysaccharide (LPS)-induced DC maturation. Using BMDCs from TOT/Tmod1 -/- mice, that were obtained by crossing cardiomyocyte-specific Tmod1 overexpressing transgenic (TOT) mice with Tmod1 +/- mice ( 37 , 38 ), we showed that Tmod1 deficiency retarded DC maturation by downregulating the expression of costimulatory molecules and inflammatory cytokines, and impaired their migration and T-cell stimulatory abilities by altering their actin cytoskeleton and cell mechanics. Furthermore, LPS-treated Tmod1-deficient DCs secreted high levels of IFN-β and IL-10, and induced immune tolerance in an experimental autoimmune encephalomyelitis (EAE) mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the roles of Tmod1 in renal function remain unclear. Green et al bred Tmod1 + /lacZ mice with cardiomyocyte-specific Tmod1 overexpressing transgenic (TOT) mice to obtain TOT/Tmod1 lacZ/lacZ mice [18, 19], which made it possible to study the consequence of Tmod1 knockout in different cell types and tissues. But unfortunately, this mouse model is not suitable to study the renal function of Tmod1 since it develops dilated cardiomyopathy, which has abnormal vasopressin production [20].…”
Section: Introductionmentioning
confidence: 99%
“…The expressions of E-Tmod41 and E-Tmod29 are driven by the alternative promoters of E-Tmod gene [ 7 ]. E-Tmod41 null mice display a mild sphero-elliptocytic anemia with osmotically fragile erythrocytes, due to the misregulation of F-actin lengths and a disrupted spectrin-actin lattice of membrane skeleton [ 8 , 9 ]. In addition to E-Tmod, there are three members in Tmod family, neuronal Tmod (N-Tmod), ubiquitous Tmod (U-Tmod), and skeletal muscle Tmod (sk-Tmod) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%